Cigarette Packs With URLs Leading to Tobacco Company Websites: Content Analysis - Weiger, Caitlin Victoria; Smith, Katherine; Hong, Amy Y; Cohen, Joanna E (JMIR Publications, 2020)
BackgroundTobacco companies include on the packaging of their products URLs directing consumers to websites that contain protobacco messages. Online media tend to be underregulated and provide the industry with an opportunity to present users with protobacco communication. ObjectiveThe objective of our study was to document the content of websites that were advertised on tobacco packs in 14 low- and middle-income countries. MethodsWe purchased tobacco packs from 14 low- and middle-income countries in 2013 and examined them for the presence of URLs. We visited unique URLs on multiple occasions between October 1, 2016 and August 9, 2017. We developed a coding checklist and used it to conduct a content analysis of active corporate websites to identify types of protobacco communication. The coding checklist included the presence of regulatory controls and warnings, engagement strategies, marketing appeals (eg, description of product popularity, luxury/quality, taste), corporate social responsibility programs, and image management. We coded brand websites separately and also described social media and other website types. ResultsWe identified 89 unique URLs, of which 54 were active during the search period. We assessed 26 corporate websites, 21 brand websites, 2 nontobacco websites, and 5 social media pages. We excluded 2 corporate websites and 14 brand websites due to limited accessible content or incomplete content. Corporate social responsibility was discussed on all corporate websites, and marketing appeals were also common. Corporate websites were also more likely to include more nonspecific (12/24, 50%) than specific (7/24, 29%) health warnings. Promotions (6/7, 86%) and sociability appeals (3/7, 43%) were common on brand websites. The small number of social media webpages in our sample used gendered marketing. ConclusionsURLs appearing on tobacco packs direct consumers to websites where users are exposed to marketing that highlights the "positive" contributions of tobacco companies on corporate websites, and extensive promotions and marketing appeals on brand websites and social media pages. It is essential that marketing regulations become more comprehensive and ban all protobacco communication, a policy that is in line with articles 5.3 and 13 of the World Health Organization Framework Convention on Tobacco Control. For countries that already ban internet tobacco advertising, enforcement efforts should be strengthened. Tobacco companies' use of URLs on packs may also be compelling for plain packaging advocacy, where all branding is removed from the pack and large graphic health warning labels are the only communication on the tobacco packaging. Future research should consider including tobacco websites in marketing surveillance.